Went to the devil : a Yankee whaler in the slave trade - Connors, Anthony J. (Bright Leaf, an imprint of University of Massachusetts Press, 2019)
"Edward Davoll was a respected New Bedford whaling captain in an industry at its peak in the 1850s. But mid-career, disillusioned with whaling, desperately lonely at sea, and experiencing financial problems, he turned to the slave trade, with disastrous results. Why would a man of good reputation, in a city known for its racial tolerance and Quaker-inspired abolitionism, risk engagement with this morally repugnant industry? In this riveting biography, Anthony J. Connors explores this question by detailing not only the troubled, adventurous life of this man but also the turbulent times in which he lived. Set in an era of social and political fragmentation and impending civil war, when changes in maritime law and the economics of whaling emboldened slaving agents to target captains and their vessels for the illicit trade, Davoll's story reveals the deadly combination of greed and racial antipathy that encouraged otherwise principled Americans to participate in the African slave trade"-- Provided by publisher
Keywords: Davoll, Edward S.; Davoll, Edward S. -- Ethics.; Slave traders -- Massachusetts -- New Bedford -- Biography.; Whaling masters -- Massachusetts -- New Bedford -- Biography.; Slave trade -- Moral and ethical aspects -- History -- 19th century.; Slave trade -- Cuba -- History -- 19th century.; Slave trade -- Africa -- History -- 19th century.; Whaling -- Massachusetts -- New Bedford -- History -- 19th century.; Seafaring life -- History -- 19th century.; New Bedford (Mass.) -- Biography.; Marchands d'esclaves -- Massachusetts -- New Bedford -- Biographies.; Traite des esclaves -- Aspect moral -- Histoire -- 19e siècle.; Traite des esclaves -- Cuba -- Histoire -- 19e siècle.; Traite des esclaves -- Afrique -- Histoire -- 19e siècle.; Baleines -- Chasse -- Massachusetts -- New Bedford -- Histoire -- 19e siècle.; Vie en mer -- Histoire -- 19e siècle.; HISTORY -- United States -- State & Local -- New England (CT, MA, ME, NH, RI, VT); Ethics; Seafaring life; Slave trade; Slave traders; Whaling; Whaling masters; Africa; Cuba; Massachusetts -- New Bedford; 1800-1899; Biography; Biographies; History; Biographies.